2011
DOI: 10.1063/1.3569825
|View full text |Cite
|
Sign up to set email alerts
|

Generation of very low energy-spread electron beams using low-intensity laser pulses in a low-density plasma

Abstract: The possibility of obtaining high-energy electron beams of high quality by using a low-density homogeneous plasma and a low-intensity laser (just above the self-injection threshold in the bubble regime) has been explored. Three-dimensional simulations are used to demonstrate, for the first time, an energy-spread of less than 1%, from self-trapping. More specifically, for a plasma density of 2×1018 cm−3 and a laser intensity of a0=2, a high-energy (0.55 GeV), ultrashort (1.4 fs) electron beam with very low ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…It has been suggested, and also observed that operating the wakefield accelerator at the threshold plasma density is advantageous, as it leads to comparatively higher stability (i.e. minimal fluctuation of electron beam parameters) and narrowenergy spread with low or almost zero background [9,80,81]. Here in the present experiment we show the effect of threshold plasma density on electron beam quality in a DLA dominated regime.…”
Section: Introductionsupporting
confidence: 58%
“…It has been suggested, and also observed that operating the wakefield accelerator at the threshold plasma density is advantageous, as it leads to comparatively higher stability (i.e. minimal fluctuation of electron beam parameters) and narrowenergy spread with low or almost zero background [9,80,81]. Here in the present experiment we show the effect of threshold plasma density on electron beam quality in a DLA dominated regime.…”
Section: Introductionsupporting
confidence: 58%
“…Theory and simulations suggest that controlling the evolution of the driving laser pulse can improve localization of electron injection, leading to the near elimination of the low-energy background [31,33,41,42]. Alternatively, matching the pulse for self-guiding (in a uniform plasma) and working close to the self-injection threshold can reduce backgrounds significantly [28,43]. Realization of this approach in the laboratory, however, appears to require very demanding laser pulse and target quality.…”
Section: Introductionmentioning
confidence: 99%
“…The same guiding can also be achieved by choosing a spot-size comparable to or slightly larger than the plasma wavelength, but with an intensity that is less than in the matched case (so that power is nearly the same). 6,8,[18][19][20] The generation of GeV-class beams, both in experiments 6,7,[9][10][11] and in simulations, 13,[19][20][21][22][23][24] has been observed in such plasmas of lower density.…”
Section: Introductionmentioning
confidence: 97%